USE OF SCRAMBLE LEARNING MODEL TO INCREASE STUDENTS' READING INTEREST IN INDONESIAN LANGUAGE SUBJECTS GRADE V STUDENTS AT SD NEGERI GUNONG KLENG MEUREUBO SUBDISTRICT - Jurna Runibar (SENSEI RESEARCH CENTER, 2021)
This study aims to determine the increase in students' reading interest by using the scramble learning model in SD Negeri Gunung Keling, Meureubo District. This type of research is classroom action research. The subjects in this study were 21 students. The data collection techniques are through tests of student learning outcomes, student activity observation sheets, teacher activity observation sheets and questionnaires. The conclusion of this research is